For domain 2x sqrt(2+x)>0
x>0,2+x>0,x>-2 combining
we get x>2
f'(x)=[1/{2x sqrt(2+x)}][{2x/(2 sqrt(2+x))}+2 sqrt(2+x)]
Answer:
-10
Step-by-step explanation:
On the number line -9 appear before -10. Thw futher the number, the smaller it gets
Answer:
X:1 2 3 4 5 Y:7 11 15 19 23.
Step-by-step explanation:
We just need to put in the values of x into the equation: y = 4x + 3.
<u>x = 1: </u>
y = 4(1) + 3
= 4 + 3
y = 7
<u>x = 2: </u>
y = 4(2) + 3
= 8 + 3
y = 11
<u>x = 3:</u>
y = 4(3) + 3
= 12 + 3
y = 15
<u>x = 4:</u>
y = 4(4) + 3
= 16 + 3
y = 19
<u>x = 5:</u>
y = 4(5) + 3
= 20 + 3
y = 23